Just Smart or Just and Smart Cities? Assessing the Literature on Housing and Information and Communication Technology. Issue 1 (2nd January 2021) - Shamsuddin, Shomon; Srinivasan, Sumeeta
ABSTRACT: Housing issues, including affordability, instability, and the search for available units, present ongoing challenges for urban inhabitants. Supporters claim information and communication technology (ICT) can solve housing problems through increased efficiency, transparency, and the creation of smart cities. However, little is known about the actual use and application of ICT data on housing issues. This article reviews and assesses recent empirical research involving housing and ICT data. Using Web of Science to identify relevant articles, we find most studies focus on housing search and prices or home sharing, which partly reflects the availability of data in these domains. Few articles use ICT data to explore housing challenges for economically vulnerable, historically disadvantaged, or marginalized groups. We discuss concerns about representation in ICT data related to housing and argue for more attention to the needs of vulnerable groups to help build more inclusive smart cities.